2022
DOI: 10.5399/osu/advjrnl.3.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Narratives of Black Women STEM Faculty: Breaking Barriers to Promote Institutional Transformation at Historically Black Colleges and Universities

Abstract: Women faculty at Historically Black Colleges and Universities (HBCUs), experience many barriers. HBCUs' rich histories of advancing racial equity have often outweighed a focus on gender equity, with issues at the intersection of race and gender receiving minimal attention. This study highlights the need for institutional transformation at HBCUs by identifying the structural factors that promote and inhibit Black women STEM faculty advancement. Interviews (n=15) were conducted with HBCU Black women STEM faculty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…In the academic context, the literature has indicated that women faculty and women faculty of color face multiple challenges at all academic employment stages of recruitment, onboarding, promotion and retention. Some examples include devaluation of scholarship (Settles et al ., 2021), ambiguous standards for tenure and promotion, lack of mentorship, lack of respect from colleagues (Bell et al ., 2021; Thomas and Hollenshead, 2001), fewer opportunities for research collaboration (Lee et al ., 2022) and students challenging their authority and scholarly expertise (Fox Tree and Vaid, 2022; Pittman, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the academic context, the literature has indicated that women faculty and women faculty of color face multiple challenges at all academic employment stages of recruitment, onboarding, promotion and retention. Some examples include devaluation of scholarship (Settles et al ., 2021), ambiguous standards for tenure and promotion, lack of mentorship, lack of respect from colleagues (Bell et al ., 2021; Thomas and Hollenshead, 2001), fewer opportunities for research collaboration (Lee et al ., 2022) and students challenging their authority and scholarly expertise (Fox Tree and Vaid, 2022; Pittman, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Lee et al (2021), Black women STEM faculty at HBCUs seek out internal and external mentorship opportunities related to scholarship and tenure. Even at HBCUs, they indicated being more likely to have their expertise questioned, and experience sexism, racism, and gendered racism (Lee et al, 2022). The authors recommended having institutional accountability and oversight, more leadership training and opportunities, and increased support for Black women STEM faculty's research agendas to facilitate institutional transformation for their success and advancement in the academy.…”
Section: Identifying Underrepresented Groups In the Academy And Their...mentioning
confidence: 99%
“…Across all disciplines, Black women comprise less than two percent of full professors in the United States (Gayles, 2022;Williams & O'Leary, 2021). Black women in science, technology, engineering, and mathematics (STEM) are even less, but it is more likely to find more at Historically Black Colleges and Universities (HBCUs) (Lee et al, 2022;Owens, 2020).…”
mentioning
confidence: 99%
“…While we may not experience issues of race identical to Black women at PWIs, Black women at HBCUs still face many intersectional challenges as we work in environments or in STEM or other disciplines with few female colleagues and fewer female academic leaders (Moore et al, 2014;Lee et al, 2022).…”
mentioning
confidence: 99%